Murder is binding eaudiobook - Barrett, Lorna (Booktown Mystery, 2010)
The streets of Stoneham, New Hampsire are lined with bookstores . . . and paved with murder.   When she moved to Stoneham, city slicker Tricia Miles met nothing but friendly faces. And when she opened her mystery bookstore, she met friendly competition. But when she finds Doris Gleason dead in her own cookbook store, killed by a carving knife, the atmosphere seems more cutthroat than cordial. Someone wanted to get their hands on the rare cookbook that Doris had recently purchased—and the locals think that someone is Tricia. To clear her name, Tricia will have to take a page out of one of her own mysteries—and hunt down someone who isn't killing by the book.